Investigation of accuracy and response time in GPS-based car mileage monitoring device - Thor, Wei Soon; M. Nafis, O. Z. (Penerbit UMP, 2022)
Nowadays, newly invented vehicle equipped with smart mileage monitoring system where notification is given when maintenance mileage reached. However, this feature is not own by old car owner. Furthermore, the available monitoring device or system in market is expensive and not accurate. Thus, in this research a Car Mileage Monitoring device with features such as mileage monitoring, maintenance service notification and car tracking system is design and develop. The objectives of this research are to investigate the accuracy percentage of the mileage monitoring system and the response time of the tracking system. In addition, a mobile application is to be fabricated to integrate with the device. In this research, STM32F103C microcontroller (Blue Pill) and A7 GPS+GSM/GPRS module is used. Moreover, Haversine formula is used to calculate distance between two coordinates. The results show that, the average percentage of accuracy for car mileage monitoring system is 91.38%. For response time, the maximum time taken is 24.54 seconds and minimum response time is 13.22 seconds. Furthermore, a mobile application with pop up maintenance notification, car tracking button and mileage reading monitor is developed. In short, the device developed is a reliable device in mileage monitoring where it has a high accuracy percentage when compare to car odometer. Besides, the device is also useful in car tracking where the response time is very short. And lastly, the device fabricated is integrated with a smart maintenance notification where notification is sent when the maintenance limit reach.